2018
DOI: 10.9738/intsurg-d-17-00028.1
|View full text |Cite
|
Sign up to set email alerts
|

Does the Implementation of Clinical Pathways Affect Hierarchical Structures Within a Surgical Department? A Qualitative Study

Abstract: Objective: To explore effects of the implementation of clinical pathways (CPs) on hierarchical structures within a surgical department. Summary of background data: CPs are care plans stipulating diagnostic and therapeutic measures along a time axis for a given condition or procedure. They are widely used in surgery. There is limited evidence to what extent CP implementation has an effect on hierarchical structures within surgical departments. Methods: Semistructured individual interviews were conducted with ke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…Eekholm et al (2021) suggested that assertive nursing leadership helped to put nursing care on the agenda, making it visible and taking time away from other activities that support the work of doctors, reclaiming time and professional identity. In a study that examined the implementation of a clinical pathway on hierarchical structures within a German surgical department (Ronellenfitsch et al 2019), participants felt that it had impacted hierarchical structures, giving staff in lower hierarchical positions more autonomy by providing detailed instructions in relation to care, for example. Another study spoke to how hierarchy may be shifted or challenged.…”
Section: Negotiating Hierarchymentioning
confidence: 99%
“…Eekholm et al (2021) suggested that assertive nursing leadership helped to put nursing care on the agenda, making it visible and taking time away from other activities that support the work of doctors, reclaiming time and professional identity. In a study that examined the implementation of a clinical pathway on hierarchical structures within a German surgical department (Ronellenfitsch et al 2019), participants felt that it had impacted hierarchical structures, giving staff in lower hierarchical positions more autonomy by providing detailed instructions in relation to care, for example. Another study spoke to how hierarchy may be shifted or challenged.…”
Section: Negotiating Hierarchymentioning
confidence: 99%